2000
DOI: 10.1509/jimk.8.1.78.19559
|View full text |Cite
|
Sign up to set email alerts
|

Educator Insights: Standardization or Adaptation of the International Marketing Mix: The Role of the Local Subsidiary/Representative

Abstract: In this article, the author suggests that the standardization versus customization issue in international marketing has important organizational aspects that are often neglected in the literature. The author parts from the traditional culture and economies of scale approaches by introducing a taxonomy of international marketing organizations based on headquarters versus subsidiary decision power and on market knowledge at headquarters. The author then suggests a typology of organizational solutions—local baron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 25 publications
(22 reference statements)
0
94
0
Order By: Relevance
“…The quality of this relationship will, to a great extent, determine how well adaptation plans are effected and accepted locally (Jain, 1989), substantially influencing brand strategy, not least in respect of implementation and control (Dibb, Simkin, Pride and Ferrell, 2006;Kotler 1999) -an issue of especial concern for international marketers, who are likely to be operating in unfamiliar, disparate and structurally complex market networks (Chung, 2009). Paradox and contradiction are inherent within nationally diverse markets and there exists a tension between the benefits to be achieved through centralized monitoring and decision making (Solberg, 2000), and the value to be had from localized understanding/interpretation of consumer intelligence (Arnold, 2000). The following propositions are advanced:…”
Section: Proposition P1bmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of this relationship will, to a great extent, determine how well adaptation plans are effected and accepted locally (Jain, 1989), substantially influencing brand strategy, not least in respect of implementation and control (Dibb, Simkin, Pride and Ferrell, 2006;Kotler 1999) -an issue of especial concern for international marketers, who are likely to be operating in unfamiliar, disparate and structurally complex market networks (Chung, 2009). Paradox and contradiction are inherent within nationally diverse markets and there exists a tension between the benefits to be achieved through centralized monitoring and decision making (Solberg, 2000), and the value to be had from localized understanding/interpretation of consumer intelligence (Arnold, 2000). The following propositions are advanced:…”
Section: Proposition P1bmentioning
confidence: 99%
“…Both Solberg (2000), and Fang, Wade, Delios and Beamish (2007), have demonstrated that subsidiaries with a long history of local association are able to gain 'deep' market intelligence and, consequently, obtain a better understanding of the local customer. It's also suggested (e.g.…”
Section: Proposition 2cmentioning
confidence: 99%
“…competition between local firms and MNEs (Poulis, Yamin and Poulis, in press), local subsidiaries' practices (e.g. Solberg, 2000), the effect of national culture on decision-making (Tayeb, 1995), etc.]. Thus, incorporating context in methodological choices and consequently in the process of theorising is a more pressing need in IB investigations.…”
Section: The Relevance Of Context For International Businessmentioning
confidence: 99%
“…-The organisational context: the study aimed at having a fairly equal representation of domestic and foreign firms in order to explore the potential influence on standardisation/adaptation of several organisational factors suggested in the international marketing literature, such as firms' size (Culpan, 1989;Whitelock and Pimblett, 1997), firms' international business experience (Cadogan, Diamantopoulos and Siguaw, 2002;Cavusgil, Zou and Naidu, 1993), orientation towards international operations (Perlmutter, 1969;Zou and Cavusgil, 2002), and a subsidiary's autonomy for locally responsive strategies (Ozsomer, Bodur and Cavusgil, 1991;Solberg, 2000).…”
Section: Purposeful Samplingmentioning
confidence: 99%
“…For example, the recent high profile takeover of Arcelor by Mittal Steel raised several interesting questions like what style of management will be used in the newly formed Arcelor-Mittal and how will the former developed country employees react to the new management from a developing country. Further, even more important which 'culture' would the management follow (Solberg, 2000). The ECMs may want to go according to the host country practices in developed countries or maybe vice-versa.…”
Section: Standardization Vs Localization and Performance Implicationsmentioning
confidence: 99%